2016
DOI: 10.1038/srep35770
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Risk Profile of c-Met inhibitors in Non-small Cell Lung Cancer: a Meta-analysis

Abstract: c-MET inhibitors are considered as a kind of novel drugs in non-small cell lung cancer (NSCLC) treatment. However, the results of different clinical studies involving c-MET inhibitors were not consistent. In this report, we performed Meta-analysis to investigate the beneficial and harmful effects of these drugs from 9 studies including 1611 patients in target drug groups and 1605 patients in control groups. As a result, patients in target drugs group had longer progression free survival (PFS) (HR 0.80, 95% CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Although the overexpression of MET protein is associated with poor prognosis in lung cancer, it was less effective as a predictive biomarker for targeted therapeutic efficacy. 78 Previous studies have found that MET overexpression has higher sensitivity and negative predictive value; 49,79 however, due to the significant intratumoral heterogeneity, immunohistochemical evaluation of MET overexpression remains challenging, limiting its use as a biomarker in the clinic. 80,81 This difficulty in screening patients for MET-targeted therapy may also partly explain the failure of MET inhibitors in recent phase III clinical trials of NSCLC.…”
Section: Overexpression Of Met/p-metmentioning
confidence: 99%
“…Although the overexpression of MET protein is associated with poor prognosis in lung cancer, it was less effective as a predictive biomarker for targeted therapeutic efficacy. 78 Previous studies have found that MET overexpression has higher sensitivity and negative predictive value; 49,79 however, due to the significant intratumoral heterogeneity, immunohistochemical evaluation of MET overexpression remains challenging, limiting its use as a biomarker in the clinic. 80,81 This difficulty in screening patients for MET-targeted therapy may also partly explain the failure of MET inhibitors in recent phase III clinical trials of NSCLC.…”
Section: Overexpression Of Met/p-metmentioning
confidence: 99%
“…Several MET TKI and MET specific antibodies have entered clinical trials [79,114]. However, based on preclinical data, acquired resistance to MET kinase inhibitors is likely to occur rapidly in cancer patients as well.…”
Section: Hgf/met Signaling Is a Hallmark Of Therapeutic Resistancementioning
confidence: 99%
“…In a meta-analysis, targeting c-MET therapies has been found to improve progression-free survival (PFS) and disease control rate (DCR) in advanced or metastatic NSCLC patients. However, c-MET inhibitors did not show the therapeutic benefits on their overall survival and objective response rate (Ye et al, 2016). It would be interesting to analyze the impact of cigarette smoke on the therapeutic efficacy of c-MET inhibitor in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%